Cover Jurnal EECCIS Vol.16 No.2 Agustus 2022 - jurnal, Editor (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2022)
Cover Jurnal EECCIS Vol.16 No.2 Agustus 2022